The correlation between export volume of rubber with production volume and market price of rubber in Malaysia: 28 years analysis / Siti Muslihah Mohd Razali - Mohd Razali, Siti Muslihah (2011)
Malaysia is one of the top producers of natural rubber in the world and in line with that, this country also one of the main exporter of the natural rubber to China. Natural rubber is important to the world as it is use widely in various sectors like plastic industries and medical industries. For Malaysia, demand for natural rubber from importer like China, USA and Germany will give opportunities to Malaysia in generate economy. There are two factors identified contribute to the export volume of rubber in Malaysia, that are production volume and market price of rubber in Malaysia itself. According to the economy theory, when the demand is high, the supply is also high. This theory is applied in the study to test whether export volume is significant with the production volume and market price of rubber. To test the significant, researcher used several method in analyzing the secondary data through Durbin-Watson,coefficient of determination, T-test, one way variance (ANOVA) and Pearson Correlation. The finding showed that there are significant relationship of export volume between production volume and market price